A Contrastive Analysis of English and Japanese Past Form of Verb from Syntactic Views - Jumli Alam Mapgun (Publikasi Indonesia, 2025)
This study explores the similarities and differences between English and Japanese past form verbs, aiming to provide insights into their linguistic characteristics for both linguistics and pedagogy. The research investigates how past tense verbs are formed in both languages and whether notable contrasts exist in their regular and irregular verb forms. Using a contrastive and descriptive method, the study compares 534 regular and 288 irregular English verbs with 302 regular and 5 irregular Japanese verbs. The findings reveal that the number of regular verbs in both languages is relatively similar, but the disparity becomes evident in the irregular verb forms, where English contains 283 irregular verbs, while Japanese has only 5. These results highlight a clear difference in the complexity of irregular verb conjugation between the two languages. The study’s significance lies in its contribution to contrastive analysis in linguistics, offering valuable insights for language learners and educators. For English and Japanese language learners, understanding these differences can facilitate more effective language acquisition and teaching practices. The novelty of this research is its focus on the comparative analysis of English and Japanese verb forms, which can aid in the development of targeted pedagogical strategies, particularly for learners transitioning between these languages. The findings suggest the importance of tailored instruction to address the challenges posed by irregular verb usage in English and the relative simplicity of Japanese verb conjugation.